FACTORS FOR FORMING STUDENTS ’VIEWS THROUGH THE FINE ART - Boboeva Zulfiya Akbarjonovna; Abdullaev Ruzimuhammad (Galaxy International Interdisciplinary Research Journal, 2021)
This article approaches the fine arts as a means of understanding the world. Art is analyzed from an artistic and scientific point of view. The relevance of the topic of the article is reflected in the insufficient study of the scientific approach in the visual arts, which is closer to scientific knowledge than other forms of artistic perception of the world, and the inadequacy of the evaluation of research